Tuberculosis Presenting as Isolated Wrist Swelling: A Case Report and Review of Literature - Oshan Basnayake; Ahamed Nihaj; Ranji Pitagampalage; Harsha Mendis (Case Reports in Surgery)
Background. Tuberculosis is a common disease entity in South East Asian countries with a significant global burden. An extra skeletal manifestation such as monoarticular TB is common, but isolated involvement of the wrist is rare. Case Summary. A 53-year-old Sri Lankan male with long-standing diabetes presented with an isolated hand swelling for a 7-month duration. His initial imaging and MRI showed multiple destructive lesions in the carpal bones, surrounding focal fluid collections and found to have caseous material intraoperatively. His histology and microbiological studies were positive for TB with no other concurrent evidence of TB elsewhere. Conclusion. Different presentations of tuberculosis should be considered when patients are presenting with atypical clinical and initial basic investigation findings in relation to monoarticular pathologies.